Osseointegration of orthopaedic implants - Goharian, Amirhossein (Academic Press, 2019)
Osseointegration of Orthopaedic Implants helps product developers at orthopedic implant manufacturers enhance the effectiveness of orthopedic implants and reduce complications, particularly in patients with osteoporotic bones. The book's expert contributors provide cutting-edge information on the latest technologies and advances available. Biomaterial researchers can use the book for basic data in the further development of orthopedic implant materials with better osseointegration. Biomechanical researchers can review related challenges and concepts of osseointegration for use in the development of implants. The book is suitable for readers from academia and industry, bridging the knowledge gap between academic based researchers, industrial based engineers, and clinical based surgeons.